2011
DOI: 10.3928/01477447-20110427-30
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Tibial Tuberosity Fracture in an Adolescent

Abstract: Avulsion fractures of the tibial tuberosity are typically sustained by adolescent males during sporting activities. Tibial tuberosity avulsions with simultaneous proximal tibial epiphyseal fractures are rare injuries. We present an unusual case of Ogden type IIIA avulsion fracture of tibial tuberosity with a Salter Harris type IV posterior fracture of proximal tibial epiphysis in a 13-year-old boy. We believe that the patient sustained the tibial tuberosity avulsion during the take-off phase of a jump while pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…This allows appreciation of the fracture configuration prior to surgery and aids planning of the reduction and fixation methods. This use of CT imaging in complex fracture patterns is also recommended by other authors 26. During the second operation, arthroscopy was used to ensure accurate fracture reduction, an approach recommended previously 25.…”
Section: Discussionmentioning
confidence: 97%
“…This allows appreciation of the fracture configuration prior to surgery and aids planning of the reduction and fixation methods. This use of CT imaging in complex fracture patterns is also recommended by other authors 26. During the second operation, arthroscopy was used to ensure accurate fracture reduction, an approach recommended previously 25.…”
Section: Discussionmentioning
confidence: 97%
“…Although the role of Osgood–Schlatter disease in the genesis of this injury is controversial [15], there are cases reported previously with this affection [2, 1619]. Osteogenesis imperfecta also has been proposed as a predisponding factor.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that obesity is associated with more frequent fracture in children [13] and weakness of physis relative to the tension applied during intense muscle loading. TTAF traumas regarding its biomechanics could lead to patellar tendon rupture, meniscal tears, cruciate ligament damage and collateral injuries [14] the type and extension of the injury will be determined by the mechanism and secondary ossification stage.…”
Section: The Cartilaginousmentioning
confidence: 99%